Associated factors, inequalities, and spatial distribution of the use of modern contraceptive methods among women of reproductive age in Peru: a population-based cross-sectional study - Díaz-Alvites, Ana Lucía (2022)
Background: The use of contraceptive methods in Peru has remarkably increased in recent decades. Nevertheless, despite the completeness and accessibility of family planning methods, modern contraceptive methods utilization in Peru remains below the South American average. Thus, this study aimed to elucidate the factors associated with modern contraceptive use, as well as the presence of inequalities and the spatial distribution in Peruvian women aged 15–49 years in 2019. Methods: A secondary data analysis was conducted using information from the 2019 Peruvian Demographic and Health Survey. We performed descriptive statistics, bivariate analysis, and Poisson multiple regression. Inequalities were estimated through concentration curves and Erreygers’ normalized concentration index. Spatial analysis included choropleth map, Global Moran’s I, Kriging interpolation and Getis-Ord-Gi* statistic. Results: The prevalence of modern contraceptive use was 39.3% among Peruvian women of reproductive age. Modern contraceptive use was directly associated with youth (aPR 1.39), women having their first sexual intercourse before the age of 18 (aPR 1.41), and being married but not together (aPR 1.87). In addition, speaking Quechua or Aymara (aPR 0.87) and having no children (aPR 0.59) were inversely associated with utilization of modern contraceptives. We found the presence of inequalities in the use of contraceptive methods (pro-rich distribution), although the magnitude was low. Spatial analysis unveiled the presence of a clustered distribution pattern (Moran’s Index = 0,009); however, there was inter-departmental and intra-departmental heterogeneity in the predicted prevalence of the use of modern contraceptives. In addition, significant hot and cold spots were found in Peru. Conclusion: Two out of five Peruvian women of reproductive age used modern contraceptives. It was associated with younger women’s age, younger age at first sexual intercourse, being married or cohabitant, among others. No substantial inequality was found in modern contraceptive use. The prevalence was heterogeneous at the intra- and inter-departmental level. Those departments located in the south, south-east, and north-east had the lowest prevalence. Therefore, nonfinancial barriers must be tackled through multi- and cross-sectoral efforts and continue to universally provide modern contraceptives.